La Victoria Lab - Elias, Jaan; Padilla-Taylor, Victor; Canales, Rodrigo (London : Yale School of Management, 2020)
Intercorp's headquarters, a 22-story, post-modern swoop of dark glass and steel, rose above an expressway in Lima, Peru. When Hernan Carranza was setting up the lab in 2014, Carlos Rodriguez-Pastor, the CEO and chairman, offered him coveted space in Intercorp's headquarters, but Carranza declined. He wanted the lab to exude a family atmosphere that would make his "labbers" feel safe to explore and innovate. He also wanted to locate the lab in a building that reminded his colleagues of Intercorp's target customer, the aspiring middle class of Peru.By 2020, LVL's role within Intercorp had evolved. While initially conceived of as an innovation lab in the model of IDEO, the lab had taken on different types of challenges, from doing deep investigations of customers to helping businesses formulate their vision statements. But was this adaptability and constant evolution a sustainable mission or should the lab define and create deeper expertise? Some thought the lab should just focus on helping companies tackle their short-term challenges, others wanted it to explore opportunities outside the mainstream. How should they choose their projects and execute upon them? How best could they demonstrate their value to the holding company?
Orginally Published InElias, J., Taylor, V.P., & Canales, R. (2020). La Victoria Lab. 20-027. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- Case studies; Small business -- Growth -- Case studies